Table of Content - -, (Journal of Arabic Language Sciences and Literature, 2024)
Table of Content:1. Manifestations of narrative language in the novel "The Thief and the Dogs"  Naguib MahfouzDr. Hadeel Kayal2. The issue of ellipses and its effect on textual cohesion: An applied linguistic study on an Umayyad poemAreej Abdullah Naeem3. Manifestations of the biblical narrative in the poetry of Mahmoud DarwishRasmiya Youssef Keadan, Professor Dr. Ihsan Al-Deek4. The Common Morpheme and Its Impact on Semantic Multiplicity: A Brief Editor on the Interpretation of the Noble Revelation by Ibn Atiyya as a Model Dr. Samah Yousef Abu Reash, Prof. Dr. Mahdi Asaad Arar5. Concealing the diacritical marks and its impact on the multiplicity of meaning in Quran, with the" Bahr al-Muhit" as an exampleFareda Jmeaan Mahmood Alkrenawi
Keywords: Journal of Arabic Language and Literature